2013
DOI: 10.1089/tmj.2012.0313
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effectiveness of Telemedicine and Traditional Surveillance in Providing Diabetic Retinopathy Screening Examinations: A Randomized Controlled Trial

Abstract: The protocol of this study is registered as ''The Comparative Effectiveness of Telemedicine to Detect Diabetic Retinopathy'' with ClinicalTrials.gov having clinical trial registration number NCT01364129. The findings and conclusions in this article are those of the author(s) and do not necessarily represent the official position of the Centers for Disease Control and Prevention. The sponsor or funding organization had no role in the design or conduct of this research. AbstractObjective: To determine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 32 publications
3
81
1
3
Order By: Relevance
“…28,29,34,36,45,46 Patients with proliferative disease were rare at all sites. From a public health perspective, our finding that most patients with DR had background DR, with almost 10% of persons with diabetes screened having maculopathy, indicates high potential for intervention in DR’s earliest phases when treatment can prevent vision loss.…”
Section: Discussionmentioning
confidence: 99%
“…28,29,34,36,45,46 Patients with proliferative disease were rare at all sites. From a public health perspective, our finding that most patients with DR had background DR, with almost 10% of persons with diabetes screened having maculopathy, indicates high potential for intervention in DR’s earliest phases when treatment can prevent vision loss.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] A randomized control trial showed that screening rates were 56% for traditional, inperson visits compared with 94% in the telemedicine group. 22 In England and Wales, DR is no longer the leading cause of blindness, which is attributed to a national DR telemedicine screening program. 23 Telemedicine for DR screening has the potential to grow rapidly as a result of these successes.…”
Section: Introductionmentioning
confidence: 99%
“…The test performed was a diabetic retinopathy examination, a test that must be performed regular on diabetic patients to avoid eyesight lost, usually performed by a trained professional, but in this case performed by telemedicine with a non-mydriatic camera, [25].…”
Section: Statistics and Impactmentioning
confidence: 99%